Fixed-interval stimulus control - Zeiler, Michael D. (1970)
Pigeons were exposed to three stimuli simultaneously, with responses to one of them, the positive stimulus, followed by food presented according to a fixed-interval schedule (FI 2-min, FI 4-min, FI 8-min, or FI 16-min). Over 90% of the total responses emitted were to the positive stimulus within a few sessions. When the birds were then studied under each of four fixed intervals, responding continued to be confined primarily to the same stimulus independent of interval size. In subsequent conditions, the three stimuli changed positions after each quarter of the interval. If the position changes did not require a response, response rate and the percentage of responses occurring to the positive stimulus decreased. If the changes did depend on a response, the complete interval appeared to be divided into four smaller intervals with a pause and then positively accelerated responding following each position change. Position changes produced by a response to any stimulus decreased control by the positive stimulus, and changes produced only by a response to it increased the percentage of responses made to that stimulus. All of the data suggested that the stimulus conditions contiguous with reinforcement controlled behavior.